2004
DOI: 10.1007/s00428-003-0969-x
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of p63 expression in squamous cell carcinoma of the oral cavity

Abstract: P63 is a recently discovered gene harbouring different isoforms by alternate splicing. The two main isoforms, TAp63 and Delta Np63, have opposite functions, being responsible for cell-cycle arrest and cell proliferation, respectively. In addition, new isoforms have been described with the same sequence as TAp63 and Delta Np63, but lacking exon 4 (Delta 4Tap63 and Delta Np73L). P63 as detected using immunohistochemistry is present in squamous cell carcinomas. To better define the role of p63 in squamous cell ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
52
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 17 publications
4
52
0
Order By: Relevance
“…Such discrepancies might be due to the monoclonal A4A antibody used in immunohistochemical analyses. Foschini et al have been suggested that A4A antibody recognizes all of p63 isoforms (TAp63, ΔNp63) that may have different functions (56). Therefore, this antibody was not able to discriminate between the different isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…Such discrepancies might be due to the monoclonal A4A antibody used in immunohistochemical analyses. Foschini et al have been suggested that A4A antibody recognizes all of p63 isoforms (TAp63, ΔNp63) that may have different functions (56). Therefore, this antibody was not able to discriminate between the different isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…Eight different protein isoforms of p63 based on alternative splicing have been described. 9,10 The aim of the present study was to further evaluate in a large case series the immunohistochemical detection of p63 as a prognostic marker especially in low-stage (stage I-II) patients of Merkel cell carcinoma. Moreover, in all cases p63 expression by immunohistochemistry and molecular analysis of its variants were studied in parallel, to compare the two different procedures.…”
mentioning
confidence: 99%
“…As the key molecule of the epithelial stratification program, 13 DNp63 expression is highly specific for squamous differentiation in neoplasia, and is usually not detected in nonsquamous carcinomas such as adenocarcinoma, small cell carcinoma or mesothelioma and others. 3,9,21,[23][24][25][26] This is valuable in the differential diagnosis of poorly differentiated malignant tumors of undetermined origin.…”
mentioning
confidence: 99%